2010
DOI: 10.1152/ajpgi.00139.2010
|View full text |Cite
|
Sign up to set email alerts
|

Ileal apical Na+-dependent bile acid transporter ASBT is upregulated in rats with diabetes mellitus induced by low doses of streptozotocin

Abstract: bile acid transporter ASBT is upregulated in rats with diabetes mellitus induced by low doses of streptozotocin. Am J Physiol Gastrointest Liver Physiol 299: G898 -G906, 2010. First published July 22, 2010; doi:10.1152/ajpgi.00139.2010.-Increased intestinal bile acid absorption and expansion of the bile acid pool has been implicated in the hypercholesterolemia associated with diabetes mellitus. However, the molecular basis of the increase in bile acid absorption in diabetes mellitus is not fully understood. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Interestingly, high levels of glucose increased the glycosylation of ASBT and enhanced its function. In this regard, we have previously shown that ASBT mRNA and protein expression were significantly elevated in rat model of diabetes mellitus (5). Our current studies provide novel evidence for a posttranslational mechanism that contributes to an increase in ASBT protein levels in response to hyperglycemia associated with diabetes mellitus.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, high levels of glucose increased the glycosylation of ASBT and enhanced its function. In this regard, we have previously shown that ASBT mRNA and protein expression were significantly elevated in rat model of diabetes mellitus (5). Our current studies provide novel evidence for a posttranslational mechanism that contributes to an increase in ASBT protein levels in response to hyperglycemia associated with diabetes mellitus.…”
Section: Discussionsupporting
confidence: 58%
“…Deglycosylation led to a decrease in ASBT function without affecting its targeting to plasma membrane (34); however, the exact mechanism by which the deglycosylation of ASBT alters its function remains elusive. Also, bile acid absorption was increased in diabetic patients and animal models of diabetes mellitus, and whether hyperglycemia affects ASBT function and N-glycosylation is not known (5,8,29).…”
mentioning
confidence: 99%
“…In the knock-out mice, this effect does not seem to be compensated by alternative mechanisms of BA absorption, such as passive absorption in the jejunum or in the colon (Dawson et al, 2003). While extrapolation from mice to humans should be done with caution due to fundamental differences between the two species, these observations support the notion that ASBT is the chief and rate-limiting step of bile acid absorption in the intestine (Annaba et al, 2010b). In contrast, we find a higher number of SLC10A1 SNPs, possibly because the resulting phenotype may be partly compensated for by other transporters capable of shuttling bile acids in the liver, such as OATP1B1 and OATP1B3.…”
Section: Bile Acid Transport: Ntcp (Slc10a1) and Asbt (Slc10a2)supporting
confidence: 69%
“…In rat primary hepatocytes, TCA improved activity of the insulin receptor and activated the insulin signaling pathway PI3K/PDK-1/AKT, with a consequent stimulation of GPCR-dependent activity of glycogen synthase (Cao et al, 2010). In a rat model of streptozotocin-induced diabetes mellitus, TGR5-mediated insulin secretion in the ileum reduced ASBT at mRNA, protein and functional levels, and decreased Slc10a2 promoter activity in Caco-2 cells (Annaba et al, 2010b). Recently, Chen and collaborators at GlaxoSmithKline showed that ASBT inhibition with 264W94 elevated GLP-1, decreased hemoglobin A1c (HbA1c) (a marker for abnormally high sugar levels) and reduced plasma glucose in Zucker Diabetic Fatty (ZDF) rats.…”
Section: Bile Acid Transport: Ntcp (Slc10a1) and Asbt (Slc10a2)mentioning
confidence: 99%
“…We next investigated whether ASBT is acylated in HEK 293 cells stably transfected with a human ASBT-V5 fusion protein (2BT cells). We have previously shown that ASBT-V5 in 2BT cells is functional and regulated in a similar manner to native ASBT (26,36). When acyl-RAC was performed in these cells, ~80% of ASBT-V5 bound to the resin, similar to what was seen in native tissues ( Figure 1D).…”
Section: Asbt Is Acylated In Native Intestinal Cells and 2bt Cellssupporting
confidence: 64%